Teknik Pemijahan Buatan Ikan Baung Hemibagrus nemurus (VALENCIENNES, 1840) di Instalasi Riset Plasma Nutfah Perikanan Air tawar, Cijeruk - Rafi Maulana Rasyad; Muhammad Rizki Maulana; Fadhil Naufal Tamirrino; Riski Awalia; Sutisna; Muh Herjayanto (AquaMarine (Jurnal FPIK UNIDAYAN ), 2023)
Hemibagrus nemurus (Siluriformes: Bagridae) or which has the Indonesian common name baung is a type of native fish that is distributed in river waters on the islands of Sumatra, Java, and Kalimantan. This fish is in great demand as a consumption fish because it has thick meat, few spines, delicious taste, and high economic value. The provision of seeds for fish cultivation activities needs to be done through hatcheries. Based on this, it is necessary to observe the artificial spawning techniques of baung at the Instalasi Riset Plasma Nutfah Perikanan Air Tawar,Cijeruk. This activity was carried out from 12 January to 12 February 2023. Observations showed that the artificial spawning technique for fish was carried out through hormone injections and artificial fertilization. The activity starts with the brood-rearing selection of mature gonad broodstock and continues with egg incubation and larval rearing. The number of eggs produced was 33,672-158,795, the egg fertilization rate was 51%, the egg hatching rate was 43%, and the total number of final larvae was 23,530.